Deed Of Roya Consent Which Made By Notary In Roya Mortage Rights Caused The Loss Of Certificate Mortage Rights In The City Of Pekalongan - Indah Nailal Muna; Hanung Hendratmoko; Anis Mashdurohatun (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
The purpose of this study was to: 1) To determine the debtor to Roya to BPN 2) To know the challenges and solutions faced by the debtor to Roya missing Encumbrance certificate 3) to determine the position of the missing Encumbrance certificate. The research method in this study, using socio-juridical to obtain data from the primary data. In a research specification is a descriptive analysis of this data is by using the applicable laws.Based on the results of data analysis concluded that: 1) The process of the debtor to Roya namely by applying Roya Land Office and bring equipment such as certificates and certificate concern Properties Roya who made by notary. 2) The obstacles faced by the debtor that is, if not made deed Roya consent by a notary then the debtor can not perform Roya or deletion in Encumbrance, while the solution is to bring the letter of loss from the police and then come before the notary to be made a deed of Roya consent by a notary to replace certificates mortgages missing. 3) Position the deed of Roya consent can not be equated with a certificate of mortgages have executorial power because it is not regulated in the legislation or firm rule. The deed of Roya consent is a requirement to carry out orderly land administration. In this case means that the position of Roya consent deed made by the notary is a custom in notarial practice.Keywords: Deed of Consent Roya; Notary; Certificate of Mortage Right.